Răspunsuri

2014-09-03T16:00:32+03:00
11/b
ecuatia devine
[2/(x+1) -4x(x-1)(x+1)  +3(X+2)/(X+2)(1-x)].(1-x)=5
paranteza patrata se restrange la
2/(x+1)-4x/(x-1)(x+1)-3/(x-1)=[2(x-1)-4x-3(x+1)]/(x+1)(x-1)=-5(x+1)/(x+1)(x-1)=5/(1-x)
atunci avem expresia
5/(1-x)  .(1-x)=
simplificand
=5 deci ceea ce trebuia demonstrat
 12/b
fractia a 2 a 
(²-4x+3)/(x²+4x+3)=(x-3)(x-1)/(x+3)(x+1)
fractia a 3 a
(x²+4x+4)/(x²-9)=(x+2)²/(x-3)(x+3)
reintregind expresia
(x+2)²/(x-3)².(x-3)(x-1).(x-3)(x+3)/(x+2)²simplificand obtinem
(x-1)/(x+1)=(x-1)(x+1)